Kepemimpinan Kepala Desa Dalam Pembangunan Desa Takulat Kecamatan Kelua Kabupaten Tabalong - Isnawati (stiatabalong.ac.id, 2026)
A fundamental issue in the administration of village governance is how to establish governmental mechanisms capable of fulfilling their mission to create a just and prosperous society. The village head, as the leader of the village government, plays a central role in village development. Improvements or declines in development during a village head’s tenure directly shape the public image of the village government as perceived by the community. This study aims to describe and analyze the leadership of the Village Head in the development of Takulat Village, Kelua District, Tabalong Regency. The research employed a descriptive qualitative approach involving seven informants. Data were analyzed using an interactive analysis model. The findings indicate that the democratic leadership of the Village Head of Takulat emphasizes active participation among village officials in decision-making processes, as well as effective coordination and communication with stakeholders, including the village community, village apparatus, the Village Consultative Body (BPD), local government, and non-governmental organizations (NGOs). The Village Head ensures that each stage of development is implemented in accordance with community needs. The findings imply that the effectiveness of village development is determined not only by administrative capacity but also by participatory, innovative, and adaptive leadership responsive to evolving community needs. This study contributes theoretically to strengthening the concept of participatory leadership at the village level and practically to promoting more responsive and community-oriented development governance.